Probing rare von Willebrand disease–causing mutations in the D4 and C-domains of von Willebrand factor - Golzar Mobayen; Sammy El-Mansi; Alain Chion; Thomas D. Nightingale; Thomas A.J. McKinnon (Research and Practice in Thrombosis and Haemostasis)
Background: von Willebrand disease (VWD) is characterized by absence or reduction of plasma von Willebrand factor (VWF) levels or reduced protein function. While the spectrum of causative VWD mutations is vast, there has been limited characterization of variants occurring within the D4-C6 domains of VWF that comprise the C-terminal portion of the molecule. Objectives: In this study, we investigated the impact of 9 putative low-frequency VWD-causing variants on VWF function. Methods: Variants were generated by site-directed mutagenesis and expressed in human embryonic kidney (HEK)293(T) cells and analyzed for expression, intracellular storage, and multimeric profile. The ability of Arg2379Cys to form dimers was assessed using an A2-CK fragment of VWF. Results: Arg2379Cys, Ser2497Pro, and Cys2639Tyr had significantly reduced secretion from HEK293T cells, while the other mutations all failed to be secreted. While cotransfection with wild-type VWF appeared to rescue expression, cotransfection with a deletion A1 construct demonstrated that only the Gly2044Asp, Glu2343Val, Ser2497Pro, and Cys2693Tyr variants could be rescued. All the variants failed to form appreciable pseudo–Weibel-Palade bodies in HEK293 cells and showed abnormal multimers in cell lysates. The Arg2379Cys variant could be overexpressed by only formed monomers and some dimers. Analysis with a VWF-A2CK protein demonstrated that in the homozygous state Arg2379Cys behaves likes a type 2A variant, while it is likely to be a type 1 variant in the heterozygous state. Conclusion: These data show that variants within the C-terminal region of VWF can dramatically impact proper VWF expression and can different impacts on VWF depending on homozygosity or heterozygosity.